Reviewers of BIBECHANA-2018 - Adhikari, Devendra (BIBECHANA, 2017)
Thanks to all reviewers who voluntarily worked as reviewer of BIBECHANA for volume 15, 2018. The contribution of reviewers is very important to maintain the high quality  the journal. We are grateful to all reviewers for their selfless contribution.BIBECHANA 15 (2018) i